Irreversible electroporation (IRE): a narrative review of the development of IRE from the laboratory to a prostate cancer treatment. (5th December 2019) - Blazevski, Alexandar; Scheltema, Matthijs J.; Amin, Amer; Thompson, James E.; Lawrentschuk, Nathan; Stricker, Phillip D.
Abstract : Introduction: Whilst whole‐gland radical treatment is highly effective for prostate cancer control, it has significant impact on quality of life and is unnecessary 'over‐treatment' in many men with screening‐detected prostate cancer. Improvements in prostate biopsy and imaging have led to increased interest in partial gland ablation to reduce treatment‐related morbidity. Several energies for focal ablation have been trialled. Irreversible electroporation (IRE) is a novel technology that ablates tissue by delivering direct current between electrodes. This narrative review documents the history of electroporation including its scientific basis, early data from pre‐clinical animal studies, and contemporary clinical outcomes from the use of IRE in prostate cancer. Methods: A literature search using the Medical Literature Analysis and Retrieval System Online (MEDLINE), the Excerpta Medica dataBASE (EMBASE), PubMed and Google Scholar was undertaken to identify historical perspectives and current clinical data relating to IRE for prostate cancer. Results: The history of electroporation and its implementation as a prostate cancer treatment was following the basic scientific principles, in vitro data, then animal studies, and now short‐ to medium‐term clinical cohorts in humans. The results of IRE on >283 patients have been published in several papers, with preserved rates of (pad‐free) continence in 91–100% of men and preserved erectile function in 79–100% of men. In‐field recurrence rates range from 0% to 33%. The current state of evidence for IRE for the treatment of primary and salvage prostate cancer is considered as Idea, Development, Exploration, Assessment, Long‐term follow‐up (IDEAL) stage 2B. Conclusions: IRE is a new focal ablative technology for the treatment of localised prostate cancer in carefully selected men. Published cohorts report encouraging short‐term oncological and functional outcomes; however, longer‐term data are needed to validate this treatment before it can be recommended for widespread clinical use.